(untitled) (Eurasian Scientific Herald, 2023)
Currently, sorption-photometric methods are widely used in the determination of heavy metals. This method is of great importance due to its sensitivity, simplicity, and less time spent on analysis. Sorption-photometric methods, one of the most modern physical and chemical methods, are widely used. Sorption-photometry is based on measuring the light absorption of colored and colorless solutions in monochromatic light